Romantik zwischen zwei Welten Potsdamer Vorlesungen zu den Hauptwerken der Romanischen Literaturen des 19. Jahrhunderts - Ette, Ottmar (AULA, 2021)
This transareal lecture inquires into the (perhaps already lost) unity of Romanticism behind the polymorphism of the Romantic discourses that took place between two worlds, Europe and America. This lecture reveals the scope of cultural relations between countries and continents in the century of nationalisms and questions the monological focus on national literatures.